Current Prevention and Management of Non Steroid Anti Inflammatory Drugs Associated Gastroenteropathy - Fransiscus Ari; Dadang Makmun (The Indonesian Society for Digestive Endoscopy, 2014)
Non-steroid anti-inflammatory drugs (NSAIDs) are the most frequently used drugs to treat inflammation and are used almost in the whole world. However, NSAID is one of the important causes of gastroenteropathy development. NSAIDs enteropathy is frequently undetected because most of them are asymptomatic and required sophisticated examinations to diagnose. Not only non-selective cyclo-oxygenases (COX) inhibitor that can cause NSAID gastropathy, but selective COX-2 inhibitors may also cause gastrointestinal complications. NSAID gastroenteropathy require further evaluation and it may differ between patients.Currently, there is no effective treatment available to treat gastrointestinal damage associated with NSAIDs administration. Identification of protective factors in gastrointestinal complication due to NSAIDs use is still a serious challenge. In this review, we will discuss the effect of NSAID administration towards gastrointestinal system, also the prevention and management strategies.Keywords: non-steroid anti-inflammatory drugs, gastroenteropathy, COX inhibitor, prevention, treatment